Generation and manipulation of light-induced orbital transport in Co/Zr/Al2O3 heterostructure probed with ultrafast terahertz emission - Haoran Xu; Yuhe Yang; Zuanming Jin; Ping Wang; Zheng Feng; Ting Wang; Wensi Yue; Cheng Chen; Feng Chen; Yiming Zhu; Yan Peng; Delin Zhang; et al. (Communications Physics)
Abstract The utilization of terahertz (THz) emission spectroscopy in femtosecond photoexcited spintronic heterostructures has emerged as a versatile tool for investigating ultrafast spin-transport in a non-contact and non-invasive manner. However, the investigation of ultrafast orbital-transport is still in the primitive stage. Here, we experimentally demonstrate the orbital-to-charge current conversion in Co/Zr/Al2O3 heterostructures. Our experimental results indicate a photoinduced orbital current (J L ) from Co propagating through Zr layer with a long-distance ballistic transport and a velocity of ~ $$0.27$$ 0.27 ± $$0.02 \, {{\rm{nm}}} \, {{{\rm{fs}}}}^{-1}$$ 0.02 nm fs − 1 . On the one hand, we demonstrate a critical pump fluence required to overcome the collisions in orbital transport, enabling a swifter flow of J L . On the other hand, a critical temperature is observed, below which the orbital transport is impeded. Finally, we observe a nearly 2.95-fold enhancement in the THz emission due to an additional conversion of the spin-to-orbital current conversion from a 1 nm thick W-insertion layer between Co and Zr layers. Our results pave the way for designing promising opto-spin-orbitronic devices and THz emitters.